TYPES, PURPOSE, AND STRATEGIES OF TEACHERâS QUESTIONS IN INDONESIAN EFL CLASSROOM OF JUNIOR HIGH SCHOOL IN BALI - Paramartha, AAGY; Ramawati, NMS; Suputra, PED (International Journal of Language and Literature, 2018)
This study was a case study which aimed to analyze the types of questions used by an English teacher, the purposes of questions asked by the teacher, and the strategy used to cope with non-responded questions. The subject of this study was an English teacher who taught seventh grade students at SMPN 1 Singaraja which is located in Singaraja, Buleleng regency, Bali, Indonesia. The data were collected through observation, interview, and video recording. The result of the analysis showed that from 241 questions, the teacher more frequently asked convergent, closed, and display questions rather than divergent, open, and referential questions. Procedural questions were also found. The teacherâs questions served several purposes such as to check studentsâ knowledge and understanding, to attract studentsâ activeness, to develop studentsâ interest and curiosity, and to stimulate students in stating information. It was also found that the teacher used seven strategies to cope with non-responded questions. This study suggested the teacher to balance the number of convergent, closed, and display with divergent, open, and referential questions to be used during teaching and learning process. In addition, the teacher should know more about the strategies for non-responded questions and the proper way to use those strategies to make the teaching and learning process runs smoothly.